"A grandes cautelas, otras mayores": importing neoliberal criminal justice policies and practices into chile. Issue 2 (3rd April 2022) - Ross, Jeffrey Ian; Barraza Uribe, Bárbara
ABSTRACT: During and since the Pinochet dictatorship, Chile has entertained and implemented new criminal justice policies and practices. Many of these ideas originated in the United States, and are tied to neoliberal initiatives. Advocates of these new initiatives, both inside and outside Chile, equate them to panaceas, and solely and/or disproportionately emphasise the benefits that can be achieved by implementing these policies and practices, while neglecting their downsides, particularly the growing empirical evidence which calls into question some of these developments. This article documents Chile's experience with the new neoliberal criminal justice initiatives that have been considered, where they have gained traction, which constituencies championed their merits, and which policies and practices were eventually chosen and implemented. This case study concludes with a series of hypotheses amenable for testing.